Use of pupillometry for the evaluation of analgesia in dogs hospitalized in intensive care: A prospective study. (May 2023) - Pouzot-Nevoret, Céline; Junot, Stéphane; Goffette, Léa; Bonnet-Garin, Jeanne-Marie; Allaouchiche, Bernard; Magnin, Mathieu
Abstract: A prospective study was performed on hospitalized conscious dogs. The objectives were: 1) to evaluate the feasibility and reliability of portable infrared pupillometry using a measure of photo light reflexes, 2) to identify parameters influencing measures, and 3) to compare parameters before and after the administration of analgesia. Twenty-nine dogs were included. Pupillometry was feasible by a single person. There was an excellent reliability for the evaluation of pupil diameter. There was poor to good reliability for the other parameters. There was an association between weight and mean pupil diameter (estimate = 0.1 mm, CI95 = [0.0; 0.1], P = 0.02), mean diameter variation (estimate = 0.2%, CI95 = [0.0; 0.4], P = 0.01), and mean velocity (estimate = 0.08 ms, CI95 = [0.03; 0.13], P = 0.002). Male dogs had a significantly larger mean pupil diameter than females (estimate = 1.3 mm, CI95 = [0.1; 2.5], P = 0.03). Independently of weight and sex, there was an association between mean pupil diameter and pain score: the higher the pain score, the lower the mean pupil diameter. There was a correlation between mean pupil diameter and morphine dose (ρ = −0.78, P = 0.0004). There was no significant difference in pupil diameter, velocity, and latency before and after analgesic administration. In conclusion, results do not support the use of PLR measurement by pupillometry as a pain assessment technique in hospitalized conscious dogs. Highlights: Pupillometry was feasible by a single person. There was an excellent reliability in the evaluation of pupil diameter. There was poor to good reliability in the other parameters. There was no significant difference in pupil parameters measured before and after analgesic administration. Results do not support the use of photo light reflex measurement by pupillometry as a pain assessment technique in hospitalized conscious dogs.